Influence of leg geometry configuration and contact resistance on the performance of annular thermoelectric generators. (15th June 2018) - Zhang, A.B.; Wang, B.L.; Pang, D.D.; Chen, J.B.; Wang, J.; Du, J.K.
Highlights: A general model for annular thermoelectric generators (ATEGs) is developed. Thermoelectric leg with constant cross-section area is suggested for the ATEGs. Effect of contact resistance on the performance of ATEGs is investigated. This paper provides a useful guideline in designing actual ATEG devices. Abstract: Geometry optimization of thermoelectric leg plays an essential role in improving the performance of thermoelectric generator (TEG). In the present study, theoretical analysis of an annular thermoelectric generator (ATEG) is carried out and a general model for investigating the influence of geometry configuration of thermoelectric leg and contact resistance on the output power, output power per unit mass and conversion efficiency is established. The results show that maximum output power per unit mass can be attained only when the cross-section area of thermoelectric leg is constant for the ideal ATEG. The optimized shape parameter is affected by the length of thermoelectric leg if the effect of contact resistance is taken into consideration, however, the calculation error of the performance induced by the variation of shape parameter is very small. In addition, the decrease in maximum conversion efficiency also varies slightly with the optimized shape parameter corresponding to the maximum output power. This study will be very helpful in designing actual ATEG devices.